Optimization of Biodiesel, Methanol and Methane Production and Air Quality Improvement - Pereira Gomes, João Fernando (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Alternative and renewable energy sources already play a very decisive role in the development of human society, helping to fulfill increasing energy demands from both industrialized and underdeveloped countries, as well as economic needs, which must comply with a decarbonized economy, decreasing the energy impact on the global environment. Among these alternative energy sources, fuels such as biodiesel, methanol, and methane are good examples of how the previous design can be achieved, as these fuels can be obtained from renewable sources, used in applications such as transportation systems, electricity generation, fuel conversion, and even for electricity storage, with reduced impact on air emissions. This Special Issue includes papers on new and innovative technical developments or approaches, reviews, case studies, as well as assessment, papers from different disciplines, which are relevant to the optimization of biodiesel, methane/methanol production systems, simultaneously resulting in air quality improvement.